The influence of temperature on optical properties of merocyanine dye thin films - Sieryk, M.M.; Doroshenko, T.P.; Grytsenko, K.P.; Navozenko, O.M.; Tolmachev, O.I.; Slominski, Yu.L.; Schrader, S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
Merocyanine dye thin films have been investigated using optical microscopy
methods. The films were deposited using the method of thermal evaporation. The
influence of substrate type and temperature on optical properties and spatial orientation
of molecules in the above films has been studied. The influence of annealing on
structural reorientation of molecules in thermally deposited dye films has been
determined.